GAME INTERAKTIF PADA PEMBELAJARAN BAHASA BALI DI SMA NEGERI 3 AMLAPURA - I Wayan Adi Upadana (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2021)
The implementation of education during the current COVID-19 pandemic has its own challenges for teachers all over the world. The pandemic requires students to study at home, which has its own obstacles for teachers in teaching. Internet-based distance learning has become a trend to carry out online learning. To give students a passion for learning, teachers can provide interesting learning using interactive game-based learning media. Interactive game applications such as Quizziz, Kahoot and Wordwall are applications that provided free of charge and very easy to use. Learning Balinese language at SMA Negeri 3 Amlapura applies the application. As the result, the motivation of students to learn Balinese language has increased and the teachers who teach Balinese language also get a positive response from the students.Keywords: interactive games, learning Balinese language